2002
DOI: 10.1017/s0022336000017315
|View full text |Cite
|
Sign up to set email alerts
|

Late Cambrian radiolarian faunas and biostratigraphy of the Cow Head Group, western Newfoundland

Abstract: Well-preserved Late Cambrian radiolarian faunas were recovered from carbonate rocks of the Cow Head Group of the Great Northern Peninsula of the island of Newfoundland, Canada. Several different faunal assemblages were recognized from three strata at Green Point, one from a stratum at Martin Point, and three from strata at Broom Point South in Gros Morne National Park. The faunas contain nine genera, five of which are new, and 33 species, all but two of which are new. The five new genera are Curvechidnina, Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
(43 reference statements)
2
28
0
Order By: Relevance
“…The material looks similar to specimens of Palaeospiculum greenpointensis Won Jenner et al 1991Webby et al 2004Tucker & McKerrow, 1995Harland et al 1990 D. bifidus Biozone Little Port Complex Kozur, Mostler & Repetski, 1996Won & Iams, 2002 ?…”
Section: Remarks This Morphotype Differs Fromsupporting
confidence: 58%
See 2 more Smart Citations
“…The material looks similar to specimens of Palaeospiculum greenpointensis Won Jenner et al 1991Webby et al 2004Tucker & McKerrow, 1995Harland et al 1990 D. bifidus Biozone Little Port Complex Kozur, Mostler & Repetski, 1996Won & Iams, 2002 ?…”
Section: Remarks This Morphotype Differs Fromsupporting
confidence: 58%
“…The number of spines and size of the test are unknown. The material shows structural relationships to Parechidnina (see Won & Iams, 2002), especially in the development of the three-dimensional mesh formed from thin radial spines or bars and curved connecting bars, and is therefore included in the genus. B) contains forms with robust and short spines, usually not more than 110 µm long and 10 µm wide (Fig.…”
Section: Remarks This Morphotype Differs Frommentioning
confidence: 99%
See 1 more Smart Citation
“…By the end of the Early Cambrian, however, faunas included recognizable stem group members of many extant phyla and classes ( Figure 5; Budd and Jensen 2000). Among protists, radiolarians first appear in Cambrian rocks (Dong et al 1997;Won and Below 1999;Won and Iams 2002), as do agglutinated, but not calcified foraminiferans (McIlroy et al 2001). Skeletons assigned to the dasyclad green algae have been reported from Cambrian carbonates in Siberia, but, by and large, algal skeletons are not a conspicuous feature of Cambrian rocks (Johnson 1966).…”
Section: Biomineralization and The Cambrian Explosionmentioning
confidence: 99%
“…A SERIES of studies of Middle Cambrian to uppermost Tremadocian (lowermost Ordovician) radiolarians performed by Kozur et al (1996), Won and Below (1999), Won and Iams (2002), and Won et al (2005Won et al ( , 2007 has shown their gradual phylogenetic diversification. These pre-Arenigian radiolarians appear to have no phylogenetic relationship to Arenigian taxa.…”
Section: Introductionmentioning
confidence: 99%